2008
DOI: 10.1007/s11606-008-0749-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Depressive Symptoms in Persons with Chronic Obstructive Pulmonary Disease

Abstract: The online version of the original article can be found at http://dx.doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 42 publications
11
110
2
4
Order By: Relevance
“…This is also consistent with the other investigators who have found that physical diseases (e.g., COPD) are related to psychiatric disorders. 15,30,31 Limitations and Strengths This study has several limitations. First, the measures used in this study were based on self-report and may include some respondent bias (e.g., individuals with negative affect might over-report depressive symptoms) or the under-reporting of cigarette smoking or doctor visits for a psychological problem.…”
Section: Discussionmentioning
confidence: 95%
“…This is also consistent with the other investigators who have found that physical diseases (e.g., COPD) are related to psychiatric disorders. 15,30,31 Limitations and Strengths This study has several limitations. First, the measures used in this study were based on self-report and may include some respondent bias (e.g., individuals with negative affect might over-report depressive symptoms) or the under-reporting of cigarette smoking or doctor visits for a psychological problem.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, all factors were included and were found that patients with rural address and single marital 16 but in rural patients it is different finding, i.e., less knowingly proved. Increase in incidence of depression and anxiety commonly in rural COPD patients can be due to less educational status, lack of health education, low socioeconomic status, poor health facility, or poor health status.…”
Section: Discussionmentioning
confidence: 80%
“…17 The severity of depression was classified according to the depression score of PHQ-9. 15 The classification is as follows: none or minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), severe (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%